Levels of Serum 25(OH)VD3, HIF-1α, VEGF, vWf, and IGF-1 and Their Correlation in Type 2 Diabetes Patients with Different Urine Albumin Creatinine Ratio - Ying Shao; Chuan Lv; Qin Yuan; Qiuyue Wang (Journal of Diabetes Research)
Objective. To investigate changes in serum 25(OH)VD3, HIF-1α, VEGF, vWf, IGF-1, and their correlation in type 2 diabetes patients at different stages of diabetic kidney disease (DKD). Methods. 502 type 2 diabetes patients were divided into three groups: Normoalbuminuric group (201 patients), Microalbuminuric group (171 patients), and Macroalbuminuric group (130 patients). Serum 25-hydroxyvitamin D3 [25(OH)VD3] was measured by chemiluminescence. Serum hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), von Willebrand factor (vWf), and insulin-like growth factor-1 (IGF-1) were determined by enzyme-linked immunosorbent assay. We detected the aforementioned serum factors in all cases and 224 control subjects. Results. Serum HIF-1α, VEGF, vWf, and IGF-1 in type 2 diabetes patients were significantly higher than those in the control group and increased with the increase of Ln(ACR), respectively (P<0.001). Serum 25(OH)VD3 was significantly lower in type 2 diabetes patients and decreased with the increase of Ln(ACR) (P<0.001). Ln(ACR) was positively correlated with duration, HbA1c, Scr, BUN, TC, LDL, TG, UA, HIF-1α, VEGF, IGF-1, vWf, and Fg and negatively correlated with 25(OH)VD3 and eGFR. Conclusion. Serum HIF-1α, VEGF, vWf, and IGF-1 may be involved in DKD process through inflammation, angiogenesis, and endothelial injury. Serum 25(OH)VD3 may have protective effects on DKD partly by inhibiting inflammation, abnormal angiogenesis, and vascular endothelial dysfunction.